Gap Analysis between Potential and Budgeted Entertainment Tax Revenues in Local Government - Krist Setyo Yulianto; Irwan Taufiq Ritonga (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study seeks to explain factors causing a significant gap between the potential and budgeted entertainment tax revenues in Wonosobo Regency Government.Design/Methodology/Approach: This study used a qualitative research approach with a case study method. The data were obtained through in-depth interviews and document content analysis.Research findings: This study uncovered that factors causing the gap between potential and budgeted entertainment tax revenues comprised the legislature's waiver to discuss the entertainment tax revenues budget intensively and in detail, executive opportunism behavior, and information asymmetry between the executive and the legislature. This study also found the phenomenon of incremental budgeting in determining the entertainment tax revenues budget.Practical and Theoretical contribution/Originality: This study provides a practical contribution for stakeholders to improve local revenue budgeting policies and offers an academic contribution as a scholarly reference regarding the opportunistic behavior of agents in setting revenue budgets, especially for small-in-size tax, for public organizations.